Study on interinstitutional collaboration in public innovation processes - Galaz, Pablo (Journal Studies of Public Policy, 2016)
This article deepens on the role of inter-institutional collaboration in processes of public innovation, through the study of two cases: the first related to the management of patients with diabetic foot in a health sub-network, and the second about the administration of three municipal heated swimming pools. On the findings of this work five key points are identified to manage collaborative innovation processes. They are the following: (i) identify if it is required to innovate by collaborative work, (ii) have teams that address the challenges to solve, (iii) ensure compliance with minimum roles needed to manage collaborative innovation, (iv) promote collaborative spaces where the management of tacit knowledge is privileged over the explicit and (v) look for evidence of the results obtained from the solutions implemented.